PENGEMBANGAN MEDIA E-BOOK INTERAKTIF FLIPBOOK MATERI AKSARA JAWA SISWA KELAS VII SMPN 13 SURABAYA - Syafaril Rochma, Maula; Dendy Andriyanto, Octo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the development process and quality of flipbook-based interactive E-Book media in Javanese script material for grade VII students of SMPN 13 Surabaya, with the formulation of the problem covering the media development process and the quality of flipbook-based E-Book media. This study uses the ADDIE development model up to the development stage of level 1, data was collected through observation, interviews, and questionnaires. The results of the questionnaire distribution in expert validation showed the category "Very Suitable" with a percentage of 97.5% from material experts, 87.5% from media experts, and 92.5% from learning experts. It can be concluded that this media is very suitable for use as an effective and systematic means of learning Javanese script.